Inhibition of the insulin receptor kinase phosphorylation by nitric oxide: functional and structural aspects - Schmid, Elmar; Hotz-Wagenblatt, Agnes; Dröge, Wulf (Antioxidants & redox signaling, 2008)
Previous studies on cultured skeletal muscle cells have indicated that the insulin-induced expression of GLUT4 transporter protein is inhibited by nitric oxide (NO). Therefore, we determined the effect of NO on the insulin-induced autophosphorylation of the insulin receptor kinase (IRK), i.e., the first step in the insulin-mediated signal transduction pathway. The experiments showed that the insulin-induced autophosphorylation of the insulin receptor β-chain is strongly inhibited by the NO donors 1,1-diethyl-2-hydroxy-2-nitrosohydrazine (DEA-NO) or S-nitroso-N-acetylpenicillamine (SNAP). The inhibitory effect was ameliorated in cells depleted of glutathione (GSH), suggesting the possibility that S-nitroso-glutathione may operate as an intermediate NO donor. Complementary experiments with different Cys → Ala mutant proteins showed, surprisingly, that all mutant proteins were inhibited by DEA-NO. Three-dimensional models of the nonphosphorylated IR β-chain nitrosylated at the accessible cysteine residues 1056, 1138, 1234, or 1245 revealed that derivatization of any of these four cysteine residues leads essentially to the same structural changes of the IRK domain. These changes involve a movement of the amino-terminal lobe against the carboxy-terminal lobe in a direction opposite to the direction of the “lobe closure” that was previously proposed to facilitate the accessibility for ATP and the expression of catalytic activity. Our findings suggest that the occurrence of several functionally relevant cysteine residues in distinct regions of the IRK protein increases the probability of regulatory redox interactions and thus the redox sensitivity of the IRK.
Published online: 19 Mar 2008
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 09.02.2021